Exploring the Essence of Curriculum and Teaching Approaches in Early Childhood Education: A Phenomenological Study of Educators' Experiences - Syahara Razaq, Siti Ulfya (Generasi: Jurnal Pendidikan Anak Usia Dini, 2024)
Backround: Early childhood education (ECE) is pivotal in establishing a foundation for lifelong learning and development. However, educators frequently encounter challenges in implementing diverse curricula and teaching methodologies. Understanding these experiences is crucial for improving educational practices and outcomes in ECE.Objective: This study aims to explore the lived experiences of early childhood educators regarding their pedagogical practices. By uncovering the essence of their challenges and successes, the research seeks to inform better curriculum design, teacher preparation, and policy development within early childhood education.Method: Using a phenomenological approach, this study involved in-depth semi-structured interviews, focus group discussions, and reflective journals with 45 early childhood educators across various educational settings. Data collection spanned 12 months and was analyzed using Colaizzi's phenomenological method.Findings and Implications: The findings yielded five major themes: (1) Curriculum Implementation Challenges, (2) Pedagogical Identity and Professional Growth, (3) Child-Centered Approaches and Authentic Learning, (4) Assessment Practices and Developmental Monitoring, and (5) Professional Development and Collaborative Learning Communities. Participants highlighted the importance of experiential learning and the integration of STEAM but noted persistent barriers, such as large class sizes and limited resources.Conclusions: The study enhances understanding of educators' lived experiences, providing valuable insights for enhancing teacher training, curriculum development, and supportive policies in early childhood education. Recommendations include improving pre-service training and fostering collaborative learning environments to better support child-centered teaching practices.